Factors affecting mortality and morbidity in patients with sternum fracture - Gul, Yeliz; Cakmak, Muharrem; Aydin, Siyami; Gul, Evrim (Bayrakol Medical Publisher, 2022)
Aim: Closed sternal fractures are deceleration injuries that occur as a result of blunt trauma. In these fractures, cardiac and great vessel injury probability is higher than that of other blunt traumas. Since they are caused by high-energy traumas, they can be accompanied by internal organ injury, chest wall injury, and head and spine traumas. Clinical findings can be very different according to other organ injuries and concomitant pathologies. In our study, we aimed to evaluate the outcomes of patients with post-traumatic sternal fracture.Material and Methods: Files of 348 patients with sternal fractures presenting to the emergency department and thoracic surgery clinic between 2011 and 2020 were evaluated retrospectively. The patients were divided into two groups as group 1 (patients with sternal fractures and other organ injuries (non -isolated sternal fractures)) and group 2 (isolated sternal fractures).Results: When the demographic distributions of the patients were evaluated, gender and etiological differences were not significant between the groups. In terms of concomitant pathologies, rib fracture, lung contusion, pneumothorax, and hemothorax were the most common in Group 1 patients, while skin abrasion was observed in Group 2. Concomitant organ injuries were most common in the liver and spleen in Group 1 patients, while there was no concomitant pathology in Group 2. CWIS was 2 in 252 of Group 1 patients, and the mean ISS was 20.07 +/- 6.51. On the other hand, CWIS was 1 in all Group 2 patients, and the mean ISS was 7.90 +/- 8.64. Group 1 ISS values were statistically significant compared to Group 2. Concomitant pathology or organ injury is the cause of increased mortality and morbidity in patients with sternum fractures.Discussion: The chest wall injury scoring system is a guide for surgery in those patients. The injury severity score, on the other hand, increases in direct proportion to the severity of the trauma and should be considered an effective parameter for demonstrating the severity of the injury.
Keywords: Morbidity; Mortality; Trauma; Sternal Fracture